A Proposed Selection Index for Jersey Cattle in Zimbabwe. (27th March 2013) - Missanjo, Edward; Imbayarwo-Chikosi, Venancio; Halimani, Tinyiko
Abstract : A multitrait selection index ( I T ) for Zimbabwean Jersey cattle was constructed. The breeding objective was defined in terms of production and functionality traits. The production component of the index included milk yield ( M ), butterfat yield ( F ), protein yield ( P ), butterfat percent ( F % ), and protein percent ( P % ), while the functional component included the somatic cell count (SCC). The index was termed as I T = 0.0004 M + 0.0109 F + 0.0313 P + 1.0004 F % + 2.4491 P % - 0.1905 S C C . The accuracy of the index was 91.1%, and the correlation between this index and the aggregate breeding objective was 0.954. A selection index is more important in the selection of sires and cows. This leads to the greatest genetic progress and hence productivity in the dairy sector. Therefore, the application of the selection index developed is necessary if the dairy cattle industry is to maximise the exploitation of genetics and to improve its relative competitive position.